Factors and Benefits that Affect Lender's Interest in Giving Loans in Peer to Peer (P2P) Lending Platform - Christiana Fara Dharmastuti; Jonathan Laurentxius (Binus Business Review, 2021)
Financial technology (fintech) is a combination of the financial industry and technology. One of the uses of fintech is the Peer to Peer (P2P) lending platform, which is a funding channel. This platform is an investment alternative that can increase borrowers' and investors' prosperity. However, P2P also has a high risk that must be considered. Lenders or investors must conduct a loan application feasibility study before giving a loan. The research examined the impact of Character, Capital, Capacity, Collateral (4C) and the benefits that lenders received, as well as the benefits of fintech on lenders' interest in placing their funds on the P2P lending platform. Data were obtained from questionnaires distributed to P2P lending users. The sampling technique was purposive sampling. The total number of respondents who returned the questionnaire was 70 respondents. However, only 53 data could be used in the research. Then, the data were analyzed using Moderated Regression Analysis (MRA). The results show that the 4C factors do not significantly affect the lenders' interest in giving loans. Meanwhile, the benefits and fintech have a significant direct impact. Fintech cannot act as a moderator variable in this model. P2P companies must provide complete information and credit analysis regarding borrowers' conditions to reduce lenders' potential risk.